The Effect of Internal Control System towards Financial Performance in PT. Kereta Api Indonesia - Muhammad Gilang Ramadhan; Eliada Herwiyanti; Wita Ramadhanti (Accounting Study Program, Faculty Economics and Business, Universitas Sebelas Maret, 2017)
This research is aimed to analyze the influence of internal control on financial performance of PT KAI. This research uses quantitative approach, with multiple linear regression analysis technique. The sampling of the research was done by using purposive sampling technique. Respondents involved in this study were 52 people, consisting of assistant managers and supervisors in PT KAI UPT Balaiyasa Manggarai. The data used is the primary data obtained from the questionnaire. Testing of the hypothesis shows three acceptable hypotheses and two unacceptable ones. The results showed that the control environment, control activities, as well as information and communication have a significant effect on financial performance. While the risk assessment is influential but not significant to the financial performance, while the monitoring has a significant negative effect on financial performance.Penelitian ini bertujuan untuk menganalisis pengaruh pengendalian internal terhadap kinerja keuangan PT KAI. Penelitian ini menggunakan pendekatan kuantitatif, dengan teknik analisis regresi linier berganda. Sampel penelitian dilakukan dengan teknik purposive sampling. Responden yang terlibat dalam penelitian ini adalah 52 orang, terdiri dari asisten manajer dan supervisor di PT KAI UPT Balaiyasa Manggarai. Data yang digunakan adalah data primer yang diperoleh dari kuesioner. Pengujian hipotesis menunjukkan tiga hipotesis yang dapat diterima dan dua hipotesis yang tidak dapat diterima. Hasil penelitian menunjukkan bahwa pengendalian lingkungan, aktivitas pengendalian, serta informasi dan komunikasi berpengaruh signifikan terhadap kinerja keuangan. Penilaian risiko memiliki pengaruh yang tidak signifikan terhadap kinerja keuangan, sedangkan pemantauan memiliki pengaruh negatif yang signifikan terhadap kinerja keuangan.